Behaviors of EFL Students on Cyber Classes: Passive presence in Google Classroom; survey of causes and attitudes - Braiek, Mustafa Salem ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2018)
Technology-integrated classrooms enhance interaction between teachers and students by providing a flexible environment for meaningful discussions and knowledge exchange. This study aimed to investigate the reasons behind students’ limited participation in Google Classroom at Misurata University, as well as to explore their attitudes toward the use of this platform. A total of 58 English Department students from the Faculty of Arts participated in the study, which employed an online questionnaire. The findings revealed that limited technical knowledge, lack of tangible incentives (e.g., extra grades), and low language proficiency were the main barriers to active engagement. Nonetheless, the results also indicated that the majority of students held positive attitudes toward using Google Classroom in their learning.